A biomechanical analysis of tibial ACL reconstruction with graft length mismatch. (16th February 2017) - Gaines, Evan B; Lau, Diana; Naziri, Qais; Hayes, Westley; Jauregui, Julio J.; Kapadia, Bhaveen H; Urban, William P; Zikria, Bashir A
Introduction: The incidence of graft length mismatch (GLM) during anterior cruciate ligament (ACL) reconstruction is reported to be up to 13%, with a rate of 20% when using bone-patellar tendon-bone (BPTB) allografts. Multiple techniques have been described to accommodate for the longer BPTB graft. As no study has compared the biomechanical properties of these methods (with cyclic loading), we evaluated the strength of four different surgical techniques used to accommodate for GLM during ACL reconstruction. Methods: A total of 32 fresh-frozen bovine tibiae and patellar tendons were divided into four groups based on the method of tibial graft fixation: (1) sutures tied over a post, (2) bone staples, (3) screws and washers, and (4) soft-tissue conversion with interference screw. Biomechanical testing was performed comparing the tensile properties of graft fixation techniques under cyclic loading. Ability to withstand 1500 cycles of load, the maximum tensile strength at load-to-failure, and the mode-of-failure were evaluated. Results: Only group 4 had all grafts intact after 1500 loading cycles, while the other groups had one graft failure at 338 (group 1), 240 (group 2), and 309 (group 3) cycles. The highest mean load-to-failure was observed in group 3 at 762 ± 173 N, which was found to be significantly higher than the other groups. The mean loads to failure in groups 1–4 were 453 ± 86 N, 485 ± 246 N, 762 ± 173 N, and 458 ± 128 N. Conclusion: While there are multiple viable techniques for fixation of a BPTB graft in the case of GLM, this study demonstrated that direct screw fixation offers the strongest construct.